Climate Change-Induced Livelihood Vulnerabilities in South Western Coastal Region of Bangladesh (Jagannath University Journal of Life and Earth Sciences, 2024)
This study focused on the impact of climate change on the livelihood of coastal people. The study used primary and secondary data to complete the study. The climatic components are changing gradually, consequently, the impact of adversity on livelihood is severe in coastal areas. This research has found the perceptions of coastal people regarding climate change and it’s devastation. Coastal people faced change-induced disasters such as cyclones, floods, tidal surges, salinity intrusion, and erosion that affected the coastal communities and their livelihoods. The study found people lost their livelihood sectors, especially agricultural activities, fish farms, fishing culture, cattle farms, business, daily working opportunities, and daily labor. However, due to the challenges during and after the disasters, they cannot easily resume their regular occupations and jobs, including agricultural activities, fishing farms, fishing and cropping businesses, daily labor, seasonal labor, and workers for fishing farms. Furthermore, the coastal people lost their property and lives, particularly settlements, agricultural land, and crops, to climate change-induced adversity. The marginal farmers and laborers are the main losers during and after disasters because they have no backup money for survival. Many of them took loans from local financial institutions and money lenders. The research will provide guidelines for the coastal community and policymakers to mitigate the impact of adversity. Jagannath University Journal of Life and Earth Sciences, 9(2): 163–178, 2023 (December)